GENDER, INEQUALITY, POVERTY, SOCIAL INCLUSION AND ECONOMIC GROWTH NEXUS IN NIGERIA - AKAMIKE , JOSEPH OKECHUKWU; OKONKWO , N. OSMOND; EJIOGU, CYNTHIA IHUOMA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
This study explores the intricate nexus between gender, inequality, poverty, social inclusion, and economic growth in Nigeria, seeking to unravel the complex interdependencies that shape the nation’s socio-economic landscape. Against the backdrop of Nigeria’s rich history and cultural diversity, this research addresses the persistent challenges that impede inclusive development. Despite marked economic growth, Nigeria faces enduring gender disparities, economic inequalities, and high levels of poverty. This study examines the nature of the nexus and the ways in which gender, inequality, poverty, social inclusion, and economic growth interact, influencing development outcomes. A comprehensive review of historical literature, policy documents, and statistical data forms the foundation of this study. Qualitative analyses are employed to dissect gender roles, economic patterns, social inclusion dynamics, and their impact on poverty and economic growth. Findings of the study revealed that historical legacies and cultural norms contribute to persistent gender disparities, limiting women’s access to education, employment, and political participation; Nigeria grapples with high levels of poverty, exacerbated by insufficient access to education, healthcare, and economic opportunities; Ethnic and religious factors shape social inclusion challenges, impacting the ability of certain groups to participate fully in economic and social activities. Based on these findings, the recommended a holistic approach, encompassing legislative reforms, targeted poverty alleviation programs, and strategies to promote social inclusion